Thermal analysis of horizontal earth-air heat exchangers in a subtropical climate: An experimental study - Lattieff, Farkad A.; Atiya, Mohammed A.; Lateef, Rudainah Ali; Dulaimi, Anmar; Jweeg, Muhsin J.; Abed, Azher M.; Mahdi, Jasim M.; Talebizadehsardari, Pouyan (Frontiers in Built Environment, 2022)
The earth-air heat exchanger (EAHX) has a promising potential to passively save the energy consumption of traditional air conditioning systems while maintaining a high degree of indoor comfort. The use of EAHX systems for air conditioning in commercial and industrial settings offers several environmental benefits and is capable of operating in both standalone and hybrid modes. This study tests the performance and effectiveness of an EAHX design in a sandy soil area in Baghdad, Iraq. The area has a climate of the subtropical semi-humid type. Ambient air temperatures and soil temperatures were recorded throughout the months of 2021. During the months of January and June, the temperatures of the inlet and outflow air at varying air velocities were monitored concurrently in ten-minute increments at each location. Further numerical and thermodynamical analyses of the measurements were conducted to reveal the influencing performance parameters. The highest temperature rises of air between the input and exit sections were determined as 12.3 ºC (January) and 17.2 ºC (June). It is found that the maximum values of effectiveness are 0.80 and 0.81, while coefficients of performance are 1.6 and 1.8 for January and June, respectively. It is also found that the EAHX shows good functionality and effectiveness, with potential energy savings for equipment for cooling and heating under different weather conditions.